Numerical investigation of VOC levels in the area of petrol stations - Kountouriotis, Alexandros; Aleiferis, Pavlos G.; Charalambides, Alexandros G. (My University, 2014)
In the area of petrol stations several Volatile Organic Compounds (VOCs) leak into the atmosphere due to the evaporation of liquid fuels, especially of gasoline that is predominantly composed of light hydrocarbons. The aim of the present study is to investigate the spatial distribution of various VOCs when leaked into the atmosphere in the area of a petrol station. The study is based on numerical simulations. The effect of wind speed and direction, as well as of air temperature has been studied. Gasoline components of different properties have been studied (e.g. pentane, iso-octane, o-xylene, toluene, benzene), as well as ethanol that is considered a new fuel blend component that can be found in different fractions in new gasoline blends worldwide. The area of flammable cloud near the source of the leak is investigated for various atmospheric conditions taking into account the lower and higher flammable limits of each compound. Lastly, the exposure to gasoline vapour is studied taking into consideration the recommended occupational exposure limits of various organisations.
Keywords: Fuels; VOC limits; Atmospheric pollution; Occupational health; Petrol station